2008
DOI: 10.1227/01.neu.0000325259.95571.20
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Tractography

Abstract: BACKGROUND AND PURPOSE:The limbic system, relevant to memory and emotion, is an interesting subject of study in healthy and diseased individuals. It consists of a network of gray matter structures interconnected by white matter fibers. Although gray matter components of this system have been studied by using MR imaging, the connecting fibers have not been analyzed to the same degree. Cerebrospinal fluid (CSF) signal intensity contamination of the fornix and cingulum, the 2 major white matter tracts of the limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Studies have shown that in cases of simple compression, the structure of neural fibers can still retain their integrity ( 22 23 ). Long-term continuous compression may lead to a decrease in the number of neural fibers or demyelination, causing a change in the FA ( 13 24 ). In a study of meningioma patients, motor weakness was found to be related to lower FA resulting from increased radial diffusivity (RD) of the CST ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in cases of simple compression, the structure of neural fibers can still retain their integrity ( 22 23 ). Long-term continuous compression may lead to a decrease in the number of neural fibers or demyelination, causing a change in the FA ( 13 24 ). In a study of meningioma patients, motor weakness was found to be related to lower FA resulting from increased radial diffusivity (RD) of the CST ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to estimate white matter structure in regions of peritumoral FLAIR-HI associated with edema in patients with high grade glioma has remained a challenge 11, 19 . Ng et al 16 reported on motor outcome in 12 patients who underwent resection of tumors adjacent to the CST. Despite lower FA in patients whose CST was affected by the presence of peritumoral edema versus those patients without edema, there were no differences between the groups in motor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that the underlying structure of white matter was largely intact in peritumoral tissue, but artifactually masked by edema. This information is critical in surgical planning of patients with high-grade gliomas who are likely to have large regions of peritumoral FLAIR-HI associated with edema causing mass effect, midline shift, and temporary clinical morbidity 16 . Deciphering intact from destroyed white matter tracts in regions of FLAIR-HI would not only assist neurosurgeons in planning the optimal surgical route, but it would also provide clinicians with information as to whether a patient’s neurological deficits are likely chronic, resulting from destroyed fiber tracts, or temporary and likely to subside once the edema and associated pathology resolve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in smaller axonal diameter and thinner myelin which may cause decreased transmission of nerve impulses[ 29 ]. Although prior studies have shown that the size of benign brain tumors was not significantly different between hemiplegia versus non-hemiplegic groups[ 30 ], these results may be due to tumor location, duration of diseases, pathological type and sample size among other factors.…”
Section: Discussionmentioning
confidence: 82%